PENGARUH INTELLECTUAL CAPITAL, UKURAN PERUSAHAAN, EARLY WARNING SYSTEM, DAN RISK BASED CAPITAL TERHADAP PROFITABILITAS - Rafi Eka Candra; Usep Syaipudin; Niken Kusumawardani (Universitas Teknokrat Indonesia, 2023)
Study this aim to study and analyze influence of intellectual capital, size companies, early warning systems (EWS), and risk based capital( RBC) against profitability on company insurance listed on the Indonesia Stock Exchange in 2017-2021. Variable independent study This is intellectual capital, size company ,liquidity ratio , claims expenses ratio , adequacy funds ratio , growth premium ratio ,own retention ratio, RBC. Variable dependent is profitability company . Technique taking sample used is purposive sampling. On study This method used is statistics descriptive , test assumption classic , test correlation pearson , test hypothesis with tool analysis used is SPSS version 26 with mark significant <0.05. Indicates :(1) intellectual capital is not influential to profitability company (2) size company influential significant to profitability company (3) liquidity ratio no influential to profitability company (4) claims expenses ratio influential significant to profitability company (5) adequacy fund ratio no influential to profitability company (6) growth premium ratio influential significant to profitability company (7) own retention ratio influential significant to profitability (8) risk based capital effect significant to profitability company.Keywords : Intellectual capital, company size, EWS, RBC, profitability company